(untitled) (Research, Society and Development, 2020)
This manuscript aims to identify the factors that generate challenges for teachers in carrying out interdisciplinary activities and integrating actions in the Programa Trajetórias Criativas. This program provides the aims to correct the distortion age-years in young people between the ages of 15 and 17 who are in the final years of primary school. Based on a theoretical-methodological approach, proposes open educational actions through an integrated work of different, favoring the development of autonomy, creation, protagonism and authorship in the group of teachers and students. The research was developed from a qualitative approach, and subjects were six teachers from a State Elementary School, located in the municipality of Alvorada/RS. The data collection took place through a semi-structured interview. The analysis of data and information was based on the Discursive Textual Analysis approach developed by Roque Moraes and Maria do Carmo Galiazzi. The analysis pointed out as factors that generate challenges: the extensive work day of teachers, absence of Internet in schools, low or non-existent financial investment for field trips, scarcity of meetings for planning, absence of students’ families within the school environment and lack of psychological follow-up in schools. It is hoped that the results of this research can assist teachers, managers, the team of the Programa Trajetórias Criativas/UFRGS and the State Secretariat of Rio Grande do Sul to recognize the challenges that teachers face daily in the development of differentiated activities. Still, it is hoped that accompanied by this recognition, there will be greater investments in public education.